Which is better for pfannensteil skin incision closure in caesarean section? Interrupted mattress suture or continuous subcuticular suture - S., Shridevi A; Bhovi, Madhusoodana R.; Prabhudeva, Prema; ., Renuka; Maitra, Camelia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Caesarean delivery is one of the most commonly performed operations in obstetrics. Postoperative comfort of the woman largely depends on the method of skin closure. Wound complications from caesarean delivery such as dehiscence or infection cause a significant emotional and economic burden in obstetric care. There are many methods and techniques for skin wound closure in caesarean section. Each technique has its own advantages and disadvantages. The aim and objective of this study was to compare the wound outcomes in Pfannensteil incisions closed with mattress sutures using nonabsorbable suture and subcuticular sutures using absorbable sutures in caesarean deliveries. Methods: It is a prospective observational study done on 216 consecutive pregnant women who were admitted to labor room for elective or emergency caesarean section. Patients undergoing caesarean section with Pfannensteil incision between February 2019 to October 2019 were included in this study. Among 216 women, 108 women had mattress sutures and 108 women had subcuticular sutures for skin wound closure. The primary outcome studied was wound complications including erythema, wound dehiscence, burst abdomen, infection and pain which was studied on postoperative day 3-7. The secondary outcome was assessed at 6 weeks follow-up in terms of pain, cosmetic appearance of scar and patient satisfaction about scar. Results: A total of 216 pregnant women undergoing caesarean section were studied who had similar baseline characteristics and risk factors. However, women with previous caesarean section were more in mattress group. The overall incidence of erythema, surgical site infection, wound dehiscence, resuturing and pain was more in mattress group and was statistically significant. During follow-up at 6 weeks, women with subcuticular sutures had cosmetically better scar and more satisfied with their scars than women with mattress sutures but the pain level was same in both groups. Conclusions: Authors conclude that compared to mattress sutures, subcuticular sutures cause significantly fewer wound complications and pain in postoperative period. Also, subcuticular sutures are associated with cosmetically appealing scars and higher patient satisfaction. But there was no difference in pain level at 6 weeks in both methods of skin closure.